Financing Social Security by Taxing Capital Income – A Bad Idea? - Lars Kunze; Christiane Schuppert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper examines the growth effects of an increase of capital income taxes with additional revenue being devoted to cut wage-related social security contributions to reduce unemployment. The analysis is carried out in an overlapping generations model with endogenous growth, unemployment and a social security system comprising pensions and unemployment benefits. It is shown that the reform not only promotes employment but may additionally stimulate economic growth. Calibrating the model to match data for the EU15 reveals that European countries can indeed gain in form of higher employment and growth if the initial capital income tax is not too high.
Keywords: H24; H55; O40; 330; Capital income taxation; social security; imperfect labor market; overlapping generations; growth; Kapitalertragsteuer; Sozialversicherungsbeitrag; Steuerwirkung; Overlapping Generations; Neue Wachstumstheorie; Beschäftigungseffekt; Arbeitsmarkt; Unvollkommener Markt; Theorie; EU-Staaten